Barbarian's touch - Dixon, Ruby, 1976- (Ice Planet barbarians, 2024)
"The next novel in the Ice Planet Barbarians series, an international publishing phenomenon - now in a special print edition with a bonus new epilogue! Lila has never been more frightened in her life, but when Rokan appears, everything changes. When I wake up on the ice planet, I'm scared of everything: This place is cold, silent, and the locals look more like blue devils than aliens. To make matters worse, one of the strangers decides I'm going to be his girlfriend and kidnaps me away from my sister. I'm completely and utterly alone. What's a girl to do? Well, this girl escapes. Of course, that means I go from the frying pan into the fire, and my situation gets even more dangerous. Just when I have no hope left, a new hero shows up. Sure, he's blue, horned, and has a tail. He's also fierce, protective, makes me purr...and thinks I'm perfect. But is what we have real or just a mating instinct?"--